Dynamic Characteristics of Approach Spike Jump Tasks in Male Volleyball Players - Wei-Hsun Tai; Hsien-Te Peng; Chen-Yi Song; Jian-Zhi Lin; Hai-Bin Yu; Li-I Wang (Applied Sciences, 2021)
The approach running spike-jump (RSJ) is a crucial technique in the sport of volleyball. Two types of RSJs are commonly used for the volleyball spike attack: (1) RSJ with one leg (RSJ-1L) and (2) RSJ with two legs (RSJ-2L). The purposes of the current study were to compare the kinematic and kinetic differences between the RSJ-1L and RSJ-2L. Ten male college volleyball players performed spike jumps by striking a stationary ball at maximal jump height. Data were collected by six infrared Qualisys motion-capture cameras (180 Hz), two AMTI force platforms (1800 Hz), and recorded by Qualisys Track Manager software. The RSJ-1L demonstrated the faster three-step approach running velocity, greater vertical GRF, and ankle, knee, and hip joint moment, but less jump height, shorter last step length and push-off time, smaller knee and hip joint flexion angles at the initial foot-contact, and knee range of motion compared to the RSJ-2L. The current study contributed to the understanding of biomechanical differences of the volleyball spike jumps and can be used to adapt to the volleyball training.